Degradation of tetrabromobisphenol a by ozonation: Performance, products, mechanism and toxicity. (November 2019) - Han, Qi; Dong, Wenyi; Wang, Hongjie; Ma, Hang; Liu, Peng; Gu, Yurong; Fan, Hongkai; Song, Xin
Abstract: This study systematically investigated the performance of ozonation on tetrabromobisphenol A (TBBPA) degradation under different ozone dosages (5.21–83.33 μmoL/L), initial solution pH (3.0–11.0) and temperatures (10–50 °C). At the same time, the generations of inorganic products (bromide ion and bromate) under different experimental conditions were evaluated and the organic products were also identified. Then, the possible mechanism was proposed and verified by the quantum chemical calculation. In addition, variations and controlling of the toxicity were also analyzed, including acute toxicity, chronic toxicity and genotoxicity. Ozonation was proved to be an efficient and promising technology for removing TBBPA from water. TBBPA of 1.84 μmoL/L could be completely degraded within 5 min under the ozone dosage of 41.67 μmoL/L in wide ranges of pH (3.0–11.0) and temperature (10–40 °C). During the degradation of TBBPA, over 65% of the average bromine ion was detected and nine products were identified. The proposed degradation pathways verified that TBBPA might undergo addition and stepwise oxidative debromination, the hydrogen extraction, and the deprotonation. The results of toxicity testing showed that ozonation could effectively control the acute and chronic toxicity of the water samples, although the toxicity increased in the initial reaction stage due to the accumulation of more toxic intermediates. Highlights: Ozonation had strong adaptability to pH (3.0–11.0) and temperature (10–40 °C). Ozonation had higher level of bromine ion (over 65%) than other reported methods. It underwent three degradation pathways verified by quantum chemical calculation. Accumulation of more toxic intermediates resulted the increase of toxicity. Acute and chronic toxicity were controlled below 0.1 and 1.0 TU, respectively.